VALUES FOUND IN “FRONT OF THE CLASS” MOVIE DIRECTED BY PETER WERNER - Novitasari, Vivid (Pusat Pengembangan Bahasa IAIN Tulungagung, 2015)
Movie as a part of audiovisual technology has a power to provide significant influences in our life. It makes us will find out the knowledge and experience as well, without having to pass in a real life. Movie contains many values including moral, social, educational values, etc. That is why through inspiring movie, such as “Front of the Class” movie, audiences can get the value conveyed in the movie and apply them to get the better life. Thus, this study aimed at knowing the values found in the “Front of the Class” movie directed by Peter Werner and to elaborate the extent of the values build up the total story of the movie. The researcher found out some values in the “Front of the Class” movie. All values found could be classified into: 1) moral value which covered high self-confident, persistent, serious, wise and righteous, independent, patient, optimist and courageous, and also humble. 2) social value included caring and kind-hearted, protective, communicative, respectful, humorous, calm, helpful, friendly, open-minded, and also wise and encouraging. 3) educational value consisted of innovative, sincere, heart-whole and inspiring. Meanwhile for answering the second research question, the researcher found out that all values; moral, social, and educational value perfectly build up the total story of the movie. Through some dialogues, prologues, and epilog, the wisdom of life could be seen directly. In addition, the intrinsic elements included plot, setting, character, conflict, characterization, etc had role to build up the total story of the movie. It made the audiences to be more easier to catch the messages.